(3GdCeKGd GdfhGOQ hGdeYGfis - (3eG TGA Gddg Hf GHQj GdeUQjs ((3GdfLa s)
(3ChdgG (B:s
(3bGd eGTGA Gddg Hf CHQi GdeUQi (B: (3Ef ef GdhGLH ai TQGFW GdMceI LeY cd eJaQb aCMHHfG Cf jMaX def JNda ef HYOfG eG MaXg GdeJbOehf dfG s
(3BNQgG (B:s
(3GdeKd GdKeGfhf ai GdbVGA (B: (3EPG bVi Gddg CeQkG cGf , aeG GdfLhe EdG HQgGf , aEf ehLO GdfLhe LYdgG OdGdI adPdc bjd (B: (3JOHQ HGdfLhe hdSJ JbVi hQJH GdfLe jaYd eG jTGA GfJgi s
(3PcQ ai GdNWHI Cf GdCeKGd NeSI hKeGfhfs
(3hGdehLhO KeGfhfs
(3gPg GdfSNI fbdJ ef fSNI cJHgG eMeO eDef GdTjQGRi SfI (B1186s
(3HgG fXGe GdJYbjHI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
Keywords: (3Gdadcs